Analisis Keterampilan Bermain Futsal UKM Bola Universitas PGRI Yogyakarta dengan Nacsport Analysis - Kustiawan, Andri Arif; Alexander, Bimo; Yunida, Tamam Sofan (MAN Insan Cendekia Jambi, 2025)
This study aims to analyse the futsal playing skills of players from the PGRI Yogyakarta University Football Club by utilising Nacsport performance analysis software as the main tool for data collection and interpretation. Futsal playing skills encompass technical, tactical, and game effectiveness aspects that are dynamic and contextual in nature, thus requiring a technology-based evaluation approach to produce an objective and measurable performance picture. This study uses a quantitative descriptive method with data collection through observation of match videos, which are then coded and analysed through the Nacsport system. The focus of the analysis includes passing, dribbling, and shooting abilities, as well as tactical indicators such as attacking positioning and defensive transition. The results of the study show that the players' passing accuracy rate is in the high category, namely 78.4%, which indicates stable coordination and game control abilities. Conversely, the effectiveness of dribbling (62.1%) and shooting (24.7%) shows that performance still needs to be improved, particularly in terms of finishing and the ability to get past opposing players. Tactical analysis reveals an attacking pattern that tends to rely on individual actions, while coordination during defensive transitions remains inconsistent, creating gaps in the defensive area. These findings illustrate that although basic technical components have developed well, tactical aspects and decision-making remain obstacles to achieving optimal performance.